A Study of Cultural Heritage and Sustainable Agriculture Conservation as a Means to Develop Rural Farms as Agritourism Destinations - Khamung, Rungnapha (Humanities, Arts and Social Sciences Studies, 2015)
Rural communities possess advantages of natural resources and culture heritage to attract agritourism development; its success will greatly increase if rural communities observe and practice self-sufficiency farming and employ sustainable agriculture practices while preserving their local cultural heritage. The objective of this paper is to investigate the rural cultural heritage, the agricultural landscape, the local traditions, the local sustainable agriculture practices, the locally practiced sustainable conservation methods, and farmers sensitivity to conservation that are appropriate for agritourism development. In addition, the conservation of local farming traditions and cultural heritage can serve as the basic foundation for agritourism destination farm development. The awareness of vernacular landscape, culturally constructed landscape, farming livelihood, cultural heritage, and traditional self-sustaining agricultural practices are the strong building blocks to foster prosperity, ecological integrity, cultural identity, social well-being, self-sufficiency, biodiversity, and sustainable conservation in rural villages that wish to become the agritourism destination.